2011
DOI: 10.4315/0362-028x.jfp-10-357
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Washing Treatments for Reducing Pathogens on Orange Surfaces and for Preventing the Transfer of Bacterial Pathogens to Fresh-Squeezed Orange Juice

Abstract: The objectives of this study were to compare the effectiveness of various washing treatments for reducing Escherichia coli O157:H7, Salmonella sp., and Listeria monocytogenes populations on orange surfaces and to measure the effect of some of these treatments in preventing the transfer of pathogens during juice extraction. Orange surfaces inoculated with L. monocytogenes or a mixture of E. coli O157:H7 and Salmonella Typhimurium were washed by water spray and then sprayed with or dipped in water at 80°C for 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…A recent study in our laboratory (14) showed that washing pathogen-inoculated oranges with hot water, lactic acid, ethanol, or chlorine resulted in reductions of 1.9 to >4.9 log CFU/cm2 for E. coli 0157:H7, 1.1 to >4.6 log CFU/cm2 for Salmonella Typhimurium, and 1.4 to 3.1 log CFU/cm2 for Listeria monocytogenes. In that study, oranges were allowed to drain for 15 min after treatment and then were sampled to measure the bacterial reduction as a result of antimicrobial application.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…A recent study in our laboratory (14) showed that washing pathogen-inoculated oranges with hot water, lactic acid, ethanol, or chlorine resulted in reductions of 1.9 to >4.9 log CFU/cm2 for E. coli 0157:H7, 1.1 to >4.6 log CFU/cm2 for Salmonella Typhimurium, and 1.4 to 3.1 log CFU/cm2 for Listeria monocytogenes. In that study, oranges were allowed to drain for 15 min after treatment and then were sampled to measure the bacterial reduction as a result of antimicrobial application.…”
Section: Introductionmentioning
confidence: 84%
“…The oranges were then ah dried in a sanitized plastic basket for 15 min at room temperature before application of treatments. This method was previously tested to ensure complete drying of the orange surfaces (14).…”
Section: Inoculation Of Orangesmentioning
confidence: 99%
“…AC concentrations of 50–200 ppm with a contact time of 1–2 min are commonly used for washing fresh produce including oranges (Parish et al., ; Suslow, ). Consequently, numerous studies have investigated the effectiveness of AC for eliminating E. coli from the surface of orange fruits (Bagci & Temiz, ; Martinez‐Gonzales, Martinez‐Chavez, Martinez‐Cardenas, & Castillo, ; Pao & Davis, ; Pao, Davis, & Kelsey, ). However, these studies have only measured elimination of bacteria using plate counts; the physiological state of the bacteria has not been determined using nongrowth‐based methods.…”
Section: Introductionmentioning
confidence: 99%
“…Citrus fruit are grown in natural, open environments and may come into contact with irrigation and postharvest processing water which are potential sources of microbial contamination (Martinez‐Gonzales, Martinez‐Chavez, Martinez‐Cardenas, & Castillo, ; Sela & Fallik, ). Hence, microbiota on fruit surfaces reflects the environmental biota where the produce is grown (Lindow & Brandl, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although total viable counts (TVCs) are not directly related to public health, they indicate the overall viable microbial load on fruit surfaces and the exposure of fruit to potential sources of contamination and conditions conducive to multiplication of microorganisms (Goodrich‐Schneider, Danyluk, Ehsani, & Friedrich, ). Additionally, their natural association with agricultural environments and fresh produce in high numbers helps to quantitatively monitor the sanitation procedures and effectiveness of packhouse processes in cleaning and disinfecting fresh produce with some degree of accuracy (Keller et al, ; Martinez‐Gonzales et al, ).…”
Section: Introductionmentioning
confidence: 99%